Zimbabwe Infrastructure Policy Review - Ringskog, Klas (World Bank, Washington, DC, 2016)
Many empirical studies have demonstrated the close relationship between a country’s economic development and its stock of infrastructure. Decades of deferred maintenance and lack of long-term financing have taken a heavy toll on Zimbabwe’s infrastructure that at one time was ranked at the top in Africa. Only the information and communications technologies (ICT) sector has been performing relatively well but its high tariffs add to the cost of doing business in Zimbabwe. The strategy in the infrastructure sectors is to encourage public private partnerships (PPPs) for the financing and execution of the different sub-projects. This strategy has been emerging in the electric power, road transport, and ICT sectors and is now being extended to water supply and sanitation. This review builds on the findings from an October-November 2013 mission that, upon the request of the Ministry of Finance, assessed the ministerial submissions for the 2014 public sector investment program (PSIP). The review concludes that the perception of the predictable policies is key for attracting responsible private partners for sustainable PPPs. The review recommends less risky options such as: (i) outsourcing operations of existing plants; (ii) lease contracts of existing plants; and (iii) sales of existing thermal plants. The review notes that the analytical multi donor trust fund (AMDTF) is programmed to close on June 30, 2014. It is of the essence to explore the possibilities to locate concessionary funding for a successor to the AMDTF given the high priority of additional studies in the power, water, and ICT sectors to prepare for the reforms suggested.